Evaluasi Pengalaman Pengguna pada Aplikasi Go-Jek Driver menggunakan Metode UX Curve - Muhammad Anas Ziauddin; Hanifah Muslimah Az-Zahra; Satrio Hadi Wijoyo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Go-jek is an app created by PT. Karya Anak Bangsa. Go-jek work with drivers all over Indonesia which they called partner. These drivers have their own application. Service improvement in Go-jek Driver application for the past year affected partner in doing their job. Data gathered using 100 curves are divided into 5 point of view including general UX, attractiveness, ease of use, utility, and degree of usage. In total, each point of view contain 20 curves. The curves then compiled to form a graphic which categorized into improving, deteriorating and stable, following the direction of the curve. From the data gathered, it generate 46 improving curve, 32 deteriorating curve and 22 stable curve. Nevertheless, every reason for movement also calculated to measure what are the reason that each respondent has for the change in curve that has been portrayed. The reason contain positive and negative reasons which categorized into 2 perception, pragmatic and hedonic. The result showed that this application has 427 reason in total from every point of view. The relation to the user satisfaction and recommendation concluded by connecting attractiveness point of view and the final result of questionnaire. Moreover, user satisfaction can be seen by looking at how respondent recommend both application to their friends.